Sandwich structures with TPMS core and printed circuit board faces - Gustavo Ferreira Malta; Pedro Henrique dos Santos Alves; Manuel Barcelos Júnior (The Journal of Engineering and Exact Sciences)
Sandwich structures are widely used in the aerospace industries due to their mechanical properties that give them high energy absorption, low density, and high mechanical strength. These structures are composed of two faces interspersed by a core that can have various geometric configurations. One of the most widely used geometric cells are honeycomb structures, highly used in structural applications since the early 20th century. However, new geometric core configurations, as well as alternative materials and manufacturing processes, are being studied for space applications. Triply Periodic Minimal Surfaces (TPMS) are lattice structures composed of periodic surface structures in three independent directions. Among the available models, the most notable TPMS structures are Schwartz-type, Diamond-type, and Gyroid-type. Since the structures are too complex to be manufactured by subtractive manufacturing, additive manufacturing is excellent, being able to produce complex structures much faster and easier. One of the most common types of 3D printing is Fused Deposition Modeling (FDM), which is based on the fusion and deposition of various materials, such as thermoplastic materials. To save space and improve the mechanical strength of Cubesats, sandwich structures are being produced using printed circuit boards (PCB) of electrical and electronic components as outer faces. These faces are called laminates and are made of thermosetting materials such as fiberglass and epoxy resin, composites, or ceramic materials. The objective of this paper is to produce sandwich panels, with a core based on the TPMS architecture. They will be printed in thermoplastic material with laminated faces used in printed circuit boards. A numerical analysis using the finite element method was performed and its testing according to ASTM C393, furthermore, this paper aims to realize an optimized TPMS core with mass distribution based on the stress profile and compare them.